EKSPLORASI KINERJA DOSEN MELALUI TRI DHARMA PERGURUAN TINGGI - Nyoto Nyoto (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The purpose of this study was to explore the performance of lecturers through the Tri Dharma of Higher Education. The research method used is qualitative with a descriptive approach. The technique of taking respondents was through purposive considerations, while the data was obtained through a closed interview questionnaire instrument and the results were processed with the help of Atlas.ti software version 8. From the coding results it is known that there is a strong relationship between lecturer performance and the Tri Dharma of Higher Education, which is stimulated by leadership factors, organizational culture, organizational commitment, and knowledge management. Knowledge management becomes the domain of performance so that knowledge transformation will strengthen the performance of lecturers in carrying out the Tri Dharma of Higher Education. Tujuan penelitian ini untuk mengeksplorasi kinerja dosen melalui Tri Dharma Perguruan Tinggi. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Teknik pengambilan responden melalui pertimbangan purposif, sementara data diperoleh melalui instrumen kuesioner hasil wawancara tertutup dan hasilnya diolah dengan bantuan software Atlas.ti versi 8. Dari hasil koding diketahui bahwa ada relasi kuat antara kinerja dosen dengan Tri Dharma Perguruan Tinggi, yang distimulasi oleh faktor kepemimpinan, budaya organisasi, komitmen organisasi, dan manajemen pengetahuan. Manajemen pengetahuan menjadi domain kinerja sehingga transformasi pengetahuan akan memperkuat kinerja dosen dalam menjalankan Tri Dharma Perguruan Tinggi.